The coordinated action of lecithin:retinol acyltransferase and cellular retinol-binding proteins for regulation of vitamin A esterification. (March 2016) - Mezaki, Yoshihiro; Fujimi, Takahiko J.; Senoo, Haruki; Matsuura, Tomokazu
Abstract: Vitamin A is a fat-soluble vitamin required for many physiological functions. The intracellular transport of vitamin A is assisted by proteins called cellular retinol-binding proteins (CRBP I/II). The absorption, storage and usage of vitamin A are regulated by a protein called lecithin:retinol acyltransferase (LRAT), a retinol-related enzyme that transfers an acyl group derived from an sn -1 position of phosphatidylcholine to retinol. LRAT is a member of the protein family which includes HRAS-like tumor suppressors (HRASLS). However, the HRASLS proteins never use retinol as an acyl acceptor. The mechanisms underlying the different substrate specificities between LRAT and HRASLS proteins are unknown. We propose in this report that LRAT physically interacts with CRBP and the LRAT–CRBP complex represents the binding pockets for both an acyl group and retinol, thus assuring the substrate specificity of LRAT.